Under the microscope : a brief history of microscopy - Croft, William J. (Series in popular science ;, 2006)
This is a brief history of the development of microscopy, from the use of beads and water droplets in ancient Greece, through the simple magnifying glass, to the modern compound microscope. The technology and optical theory are developed in a straightforward manner, and this leads to a description and explanation of the most modern technologies in electron microscopy, and scanning electron microscopy as well as the new scanning probe microscopies. A series of very interesting applications of the various microscopic techniques are described. The most recent pioneering techniques in near field a.